2022
DOI: 10.1002/jnm.2996
|View full text |Cite
|
Sign up to set email alerts
|

Traffic aware cyclic sleep‐based power consumption model for a passive optical network

Abstract: For a network, a power consumption model is an important tool to test the performance of a network process for different traffic loads. In a Passive optical network (PON), the optical network unit (ONU) is responsible for the major power consumption of PON. Both IEEE and ITU have standardized a cyclic sleep process (CSP) for ONU energy conservation. In next-generation PON; TWDM and XGS PON, the ONU power contribution has increased further due to higher number of ONUs and ONU being tunable. Therefore, an accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…While these earlier works have addressed essential aspects of bandwidth allocation and network performance, they have not considered the crucial energy conservation factor, which is becoming increasingly important today. Previous studies have neglected the energysaving processes recommended by ITU-T, such as the cyclic sleep process (CSP), the cyclic doze mode (CDM), and the watchful sleep mode (WSM) [34], [35], [36]. This knowledge gap highlights the need for new research incorporating these energy-saving processes into the design of network scheduling mechanisms.…”
Section: Related Workmentioning
confidence: 99%
“…While these earlier works have addressed essential aspects of bandwidth allocation and network performance, they have not considered the crucial energy conservation factor, which is becoming increasingly important today. Previous studies have neglected the energysaving processes recommended by ITU-T, such as the cyclic sleep process (CSP), the cyclic doze mode (CDM), and the watchful sleep mode (WSM) [34], [35], [36]. This knowledge gap highlights the need for new research incorporating these energy-saving processes into the design of network scheduling mechanisms.…”
Section: Related Workmentioning
confidence: 99%
“…Reference [14] reported that large number of students dropped out a major worry of higher education organizations. It greatly influences the fee of students and discarded public resources.…”
Section: Relate Workmentioning
confidence: 99%